KONSTRUKSI HAM NASIONAL : Kajian Aliran – Aliran Pemikiran Hak Asasi Manusia dalam UU Nomor 39 Tahun 1999 Tentang Hak Asasi Manusia - UNGGUL SUGIHARTO, UNGGUL SUGIHARTO (Program Magister Ilmu Politik, Universitas Diponegoro, 2013)
Relations between state with citizens is an important aspect in the life processes ofpolitical, social and cultural framework, nation and state. The relation is usually reflected in alegislation that substantial rights and obligations of citizens by the State itself. One productlegislation is a reflection of the relationship between the State and its citizens is Act Number39/1999 on Human Rights. Act number 39/1999 be a milestone in relations clarity Staterelations with citizens on a national scale which is also mandated MPR XVII/MPR/1998 ofCharter of Human Rights. Act number 39/1999 on Human Rights set to be the right of anycitizen, or duties and obligations of the State in respected, protection, assurance andimplementation of the human rights of citizens. This legislation recognized products have avariety of legal reference sources such as the UN Universal Declaration of Human Rights aswell as a variety of ratification of international conventions. Reference sources in act number39/1999, of course, loaded with a variety of concepts and schools of thought about humanrights in particular. This means that the act number 39/1999 is not resistance to the variousschools of thought about human rights. The interesting aspect of a big question, that is, aslegislation which regulate the various components of the national Human Rights Act actually39/1999 is influenced by the flow of what the human mind and what the most influentialschools of thoughtKey word: Legislation, Human Rights and Thought